Upaya Membangun Kesadaran Lingkungan Melalui Kegiatan "Eco-Kids" di TK Desa Bicak - Fatharisa I. Maulida; Rima N. K. S. Sulthoni; Mohammad G. P. Syahtoni; Sjarief Hidajat (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2024)
Education is an effort that is made consciously and structured to create a learning environment that allows students to actively develop their abilities.One of the important characters that must be grown through education is concern for the environment. Environmental education (PLH) is essential, particularly at the Kindergarten level, to increase environmental awareness from a young age. The "Eco-Kids" program is an initiative aimed at increasing environmental awareness in children through practical and fun activities. This community service activity took place in Bicak Village, Mojokerto with the participation of kindergarten children. The socialization material includes the introduction and management of waste and the impact of littering which is conveyed through educational video media, direct practice of sorting organic and inorganic waste, singing together, ending with the activity of decorating garbage cans. Additionally, mini games were conducted to assess the children's comprehension of the material. The "Eco-Kids" program is carried out in three kindergartens, namely RA. Miftahul Ulum, TK. Cempaka, and Nusa Indah Kindergarten, with 70 participants in total. The "Eco-Kids" program is expected to encourage a sense of environmental responsibility, protect and preserve the environment, and involve children in real activities such as sorting garbage and painting garbage cans.